2020
DOI: 10.1155/2020/1409038
|View full text |Cite
|
Sign up to set email alerts
|

miR-214-3p Attenuates Sepsis-Induced Myocardial Dysfunction in Mice by Inhibiting Autophagy through PTEN/AKT/mTOR Pathway

Abstract: Aims. More than half of the patients with sepsis would develop cardiac dysfunction, which is termed as sepsis-induced myocardial dysfunction (SIMD). Previous studies suggest that autophagy may play an important role in SIMD. The present study investigated whether miR-214-3p could attenuate SIMD by inhibiting autophagy. Main Methods. In this article, we investigated the role of autophagy in a mouse model of cecal ligation and puncture (CLP). The stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…In their study, myocardial inflammation, apoptosis, and dysfunction were decreased when the miR-214 expression was enhanced via its precursor, and, vice versa, they were worsened by its inhibitor. In a different study, it was demonstrated that miR-214-3p inhibits autophagy via the PTEN/AKT/mTOR pathway [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study, myocardial inflammation, apoptosis, and dysfunction were decreased when the miR-214 expression was enhanced via its precursor, and, vice versa, they were worsened by its inhibitor. In a different study, it was demonstrated that miR-214-3p inhibits autophagy via the PTEN/AKT/mTOR pathway [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is a phosphatase that regulates various cellular signaling pathways and has tumor suppression properties. Some of the aforementioned studies demonstrated that PTEN is targeted by miRNAs in sepsis-induced cardiac damage [ 53 , 59 , 60 ]. A further complication in understanding the role of miRNAs in septic myocardial injury is represented by lncRNAs, as evidenced by some research studies mentioned above [ 45 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact molecular mechanism by which LARS mutation influences human ILFS1 needs to be determined using knock-in animal models, wherein a corresponding mutation is introduced into the zebrafish larsb locus. Moreover, there is increasing evidence for autophagy being associated with many diseases, including sepsis, Parkinson's disease, and Alzheimer's disease 40 42 . Hence, autophagy regulation by LARS may lead to new therapeutics for these related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The exact molecular mechanism by which LARS mutation influences human ILFS1 needs to be determined using knock-in animal models, wherein a corresponding mutation is introduced into the zebrafish larsb locus. Moreover, there is increasing evidence for autophagy being associated with many diseases, including sepsis, Parkinson's disease, and Alzheimer's disease [29][30][31] . Hence, autophagy regulation by LARS may lead to new therapeutics for these related disorders.…”
Section: Discussionmentioning
confidence: 99%